The Role of Inclusive Education in Reducing Discrimination in Schools - Muhammad Adip Fanani; M Iqbal Abdurrohman (Penerbit Hellow Pustaka, 2025)
Inclusive education has an important role in reducing discrimination in schools by providing access to equitable and quality education for all students, including those with special needs. The research method used is library research with data analysis from various literature sources related to the Role of Inclusive Education in Reducing Discrimination in Schools. This study explains the benefits of inclusive education, the challenges of its implementation, and strategies that can be applied to create a learning environment that supports diversity. Inclusive education in reducing discrimination in schools, including how this approach can promote social inclusion and equity in education.